Convergence and divergence of private law in Asia / edited by Gary Low. - Low, Gary (Lawyer) (Cambridge University Press, 2022)
There have been an increasing need for greater integration of many Asian economies, either within the confines of ASEAN or on a more geo-economically strategic scale including major Asian jurisdictions like China, Japan, and Korea. A number of key personalities within the regional legal fraternity have advanced views that such integration ought to occur through the harmonization of legal rules, arguing that in doing so, uncertainty and other transaction costs would be reduced and commercial confidence within the region concomitantly increased. This edited volume brings together eminent and promising scholars and practitioners to investigate what convergence and divergence means in their respective fields and for Asia. Interwoven in the details of each tale of convergence is whether and how convergence ought to take place, and in so choosing, what are the attendant consequences for that choice.